Glocalization in CLIL: Analyzing the training needs of in-service CLIL teachers in Taiwan and Spain - Pineda-Hernández, Inmaculada Concepción; Tsou, Wenli; Chen, Fay (Taylor and Francis, 2022)
Glocalization is the local adaptation of global trends, and though it has been extensively studied in other fields, there has been a lower emphasis on it in pedagogy. Glocalization is especially relevant in education given that pedagogical approaches to language learning such as Content and Language Integrated Learning (CLIL) and English as a Lingua franca (ELF) have gained global popularity. The current paper examines beliefs, attitudes, and training needs of in-service CLIL teachers from two contexts: Taiwan and Andalusia (Spain). To this avail, a common online questionnaire was designed. 244 teachers participated in the study, 158 from Taiwan and 86 from Spain. Data have been analyzed quantitatively using the constant comparative model. Results indicate that CLIL teachers have considerable methodological and linguistic needs. Notably, while all teachers indicated a metalinguistic identity aligned with ELF, Andalusian teachers expressed a higher need for linguistic training than Taiwanese teachers and put language accuracy prior to content knowledge when assessing bilingual learning effectiveness. Conversely, Taiwanese bilingual teachers valued content training for themselves and assessment in content knowledge for learners. The present study concludes with identifying different training needs in each context thus supporting the notion of glocalizing CLIL teacher training.
Keywords: Segunda lengua - Adquisición; CLIL; ELF; Glocalization; Teacher Education; Taiwan; Spain